Sustentabilidade na construção civil: crítica, síntese, modelo de política e gestão de empreendimentos - Silvio Romero Fonseca Motta (2009)
Our development model is characterized by high consumption of natural resources and environmental degradation. The limitations of natural resources quantity as well as the environmental and climate changes resulting from these characteristics show that this framework is unsustainable. The awareness of the need for a new development modelthat seeks sustainability is increasingly present in society. The construction sector, seen as producing agent of the built environment, is essential in this new paradigm, and has to adopt new practices based on concepts consistent with sustainability. There are many discussions and studies that seek the concepts and practices necessary for sustainability in the sector, however it is necessary that information be better targetedand integrated. This paper aims to contribute to this challenge by discussing theoretical concept of sustainability in the built environment and proposing a model of practical application of it. To do this, discuss the current state of sustainability in construction through the study of sustainability concepts related to our economic development model, and the perception of them in construction. Also is analyzing the sustainabilitypractices already adopted in the projects construction. The results of these studies are presented through a critical analysis of the current state of sustainability in relation to the historical moment and the civil construction. Some statements and questions of the construction sector reality are exposed. Using the methods of synthesis of this knowledge and a holistic approach, the paper presents a concept of sustainabilityrelated to the built environment and civil construction project. The proposed concept has open and inventive characteristics, understood as fundamental aspects of sustainability, and shows potential to contribute to new knowledge and sustainability practical application in the sector. The work also develops a model of politic and management ofprojects, including a management decision tool, allowing a consistent application of the concepts proposed. This has been valid as a first approximation of experimental intention and has possibilities to be tested or falsified.